Macronutrient Intake Among Multidrug-Resistant Tuberculosis Patients in Three Referral Hospitals in Indonesia - Nina Mariana; Anggi Gayatri; Indah Suci Widyahening; Ano Rosdiana; Vivi Setiawaty; Purwantyastuti Ascobat (GLOBAL HEALTH SCIENCE GROUP, 2025)
Poor nutritional status, such as macro- and micronutrient deficiencies, might lead to worse clinical outcomes in multidrug-resistant tuberculosis (MDR-TB) patients. This study aimed to describe the macronutrient intake among MDR-TB patients and then compare those findings with the Indonesian recommended dietary allowance (RDA). A cross-sectional study of MDR-TB outpatients aged 18-65 years treated with the nine- or 18-month regimens at the end of the first month of treatment was conducted. Macronutrient intake data were obtained from a food consumption survey (24-hour food recall) of MDR-TB outpatients that was conducted by interviewing, recording, and then analyzing using NutriSurvey software, and compared with the RDA of the Ministry of Health of Indonesia. There were 63 outpatients with MDR-TB. The mean age was 38 (SD 12) years, and most of the patients were male (58.7%). Nutritional status based on BMI < 18,5 kg/m2 was observed in 43 patients (68.3%). According to the survey, after the end of the first month of MDR-TB treatment, the median (min–max) daily intake of energy was 1386.5 (519.4 – 2963.6) kcal per day, and the mean of protein was 49.6 (SD 23.0) grams per day. The median (min-max) daily intake of fat was 43.0 (1.1-170.6) grams per day, and the mean carbohydrate was 209.16 (87.9) grams per day. The proportions of energy, protein, fat, and carbohydrate deficiency were 85,7%, 68,8%, 74,6%, 90,5%, respectively. Macronutrient intake among MDR TB patients in this study was lower than the Indonesian recommended dietary allowance. These findings indicate that additional food intake and dietary counseling are needed in MDR-TB patients in Indonesia.